Performance of the BioFire Blood Culture Identification 2 panel for the diagnosis of bloodstream infections. Issue 7 (July 2022) - Peri, Anna Maria; Bauer, Michelle J.; Bergh, Haakon; Butkiewicz, Dominika; Paterson, David L.; Harris, Patrick NA.
Abstract: Background: Conventional blood cultures methods are associated with long turnaround times, preventing early treatment optimization in bloodstream infections. The BioFire Blood Culture Identification 2 (BCID2) Panel is a new multiplex PCR applied on positive blood cultures, reducing time to pathogen identification and resistant markers detection. Methods: We conducted a prospective observational study including positive blood cultures from Intensive Care Units and Emergency Departments and performed BCID2 in addition to conventional testing. Concordance between the two methods was assessed and BCID2 performance characteristics were evaluated. Resistance markers detected by BCID2 were confirmed by in-house PCR. Whole genome sequencing was performed in discordant cases. Results: Among 60 monomicrobial blood cultures, BCID2 correctly identified 55/56 (91.7%) on-panel pathogens, showing an overall concordance of 98%. In 4/60 cases BCID2 did not detect any target and these all grew BCID2 off-panel bacteria. Only one discordant case was found. Sensitivity and specificity for Gram-positive bacteria on monomicrobial samples were 100% (95% CI 85.8–100%) and 100% (95% CI 90.3–100%) respectively, while for Gram-negatives 100% (95% CI 87.7–100) and 96.9% (95% CI 83.8–99.9%), respectively. Among two polymicrobial blood cultures, full concordance was observed in one case only. BCID2 identified antimicrobial resistance genes in 6/62 samples, all confirmed by in-house PCR (3 mecA/C S. epidermidis, 3 bla CTX-M E. coli) . Estimated time to results gained using BCID2 as compared to conventional testing was 9.69 h (95% CI: 7.85–11.53). Conclusions: BCID2 showed good agreement with conventional methods. Studies to assess its clinical impact are warranted. Highlights: Blood cultures have long turnaround times preventing early targeted therapy in sepsis. BCID2 is a multiplex PCR for pathogens and resistances on positive blood culture. BCID2 showed excellent agreement with conventional methods. BCID2 significantly reduced time to results as compared to culture-based methods. Rapid diagnostic methods may lead to early treatment and improved outcomes in sepsis. Abstract : Bloodstream infection; Sepsis; Blood culture; Molecular diagnostic techniques.